Development of de novo nonalcoholic fatty liver disease following pancreatectomy. Issue 4 (27th January 2023) - Patel, Vanisha; Shah, Parth; Ludwig, Daniel R.; Hammill, Chet W.; Ashkar, Motaz
Abstract : De novo non-alcoholic fatty liver disease (NAFLD) after pancreatectomy is a recognized phenomenon; however, its pathophysiology is poorly understood. This study aimed to determine the incidence and identify peri-operative risk factors for the development of de novo NAFLD within various pancreatectomy groups. This single-center retrospective cohort study included patients who underwent pancreatectomy between 2000 and 2020. The incidence rate of de novo NAFLD and time to diagnosis were recorded across patients with malignant versus benign indications for pancreatectomy. The overall incidence of de novo NAFLD after pancreatectomy was 17.5% (24/136). Twenty-one percent (20/94) of patients with malignant indications for surgery developed NAFLD compared to 9.5% (4/42) with benign indications ( P = .09). Time to development of hepatic steatosis in the malignant group was 26.4 months and was significantly shorter by an average of 6 months when compared to the benign group (32.8 months, P = .03). Higher pre-operative body mass index was associated with new-onset NAFLD ( P = .03). Pre-operative body mass index is a significant predictor for de novo NAFLD and highlights a group that should be closely monitored post-operatively, especially after resections for pancreatic malignancy.